ANALISIS KETIMPANGAN WILAYAH KABUPATEN/KOTA PROVINSI SULAWESI UTARA - Reno Raven Derek; Olly Esry Laoh; Sherly Jocom (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The aim of this study was to analyze the level of inequality in regencies / cities in North Sulawesi Province and to analyze the factors that influenced regional disparities that occur in regencies / cities in North Sulawesi Province. Research used secondary data. Data were collected and obtained from the Central Statistics Agency of North Sulawesi Province and related Government Agencies for the period of 2013 to 2017 in the form of GRDP, population, economic potential, and various other secondary data. The data obtained were grouped and processed using the MS Excel application. Method of data analysis was the Williamson Index Method, which was a method of measuring regional inequality. The results showed that North Sulawesi Province experienced low inequality in 2013 to 2016 and high inequality in 2017 with a value of 0.55. Factors affecting North Sulawesi's regional inequality were the concentration of regional economic activity, investment allocation, low levels of mobility and production factors between regions, differences in the demographic conditions of the region and less smooth of trade in land, sea and air transportation. The Williamson Index in 2013-2014 was worth of 0.48, in 2015 it was worth of 0.47, in 2016 it was worth of 0.48 and in 2017 it was worth of 0.55. This showed that the inequality in North Sulawesi from 2013 to 2016 was low but in 2017 was high.Keywords: Regional Inequality, Index Williamson